Analisis Faktor yang Mempengaruhi Tingkat Kemandirian Keuangan Daerah Kabupaten Bangka Tahun 2019-2023 - Sari, Nurrohma Angelina (ECONOMETRICS:Journal of Sustainable Economics and Management, 2025)
In Indonesia, the central government delegates authority to district/city governments to manage their regional affairs aimed at improving public services, promoting regional economic growth, and strengthening democracy. A crucial aspect in the success of regional autonomy is financial independence. This study is useful for analyzing aspects that contribute to the financial independence ratio of the Bangka Regency with tax effectiveness, contribution of retributions, and capital expenditure as variable X and local original income as variable Y. The approach of this study is quantitative descriptive analysis with a sample of 20 data points from the realization report of the Bangka Regency budget from 2019-2023. The data analysis technique used is multiple linear regression analysis. The results of the data analysis indicate that the effectiveness of taxes has a positive but not significant effect on local revenue. The contribution of fees has a negative but significant effect on local revenue. Capital expenditure has a positive and significant effect on local revenue in Bangka Regency